2012
DOI: 10.15835/nsb448185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium and Lead on Quantitative and Essential Oil Traits of Peppermint (Mentha piperita L.)

Abstract: Cadmium (Cd) and lead (Pb) are particularly noteworthy metals that can pollute the air, soil and water contributing to serious environmental problems. Tests were done on concentrations of Pb and Cd; treatments tested in the experiment were as follows; Cd concentrations (10, 20, 40, 60, 80, 100 ppm) and concentrations of Pb (100, 300, 600, 900, 1200, 1500 ppm) and control. Tests were done on Mentha piperita L. in a greenhouse, arranged as a randomized complete block design with three replications. Rhizomes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Similarly, the exposition of Anethum graveolens and Ocimum basilicum to Cd, Pb and Cu showed no clear trend of variation (ZHELJAZKOV et al, 2006). Moreover, Mentha piperita cultivated with Pb and Cd, under maximum concentration of 100 and 1500ppm respectively, showed a significant reduction of essential oil yield, which was mainly associated with the reduction of biomass, number of leaves and total leaf area (AMIRMORADI et al, 2012). Table 2-Relative percentages of essential oil constituents from leaves of M. arvensis grown with increasing concentrations of Pb and Cd applied separately to the soil.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the exposition of Anethum graveolens and Ocimum basilicum to Cd, Pb and Cu showed no clear trend of variation (ZHELJAZKOV et al, 2006). Moreover, Mentha piperita cultivated with Pb and Cd, under maximum concentration of 100 and 1500ppm respectively, showed a significant reduction of essential oil yield, which was mainly associated with the reduction of biomass, number of leaves and total leaf area (AMIRMORADI et al, 2012). Table 2-Relative percentages of essential oil constituents from leaves of M. arvensis grown with increasing concentrations of Pb and Cd applied separately to the soil.…”
Section: Discussionmentioning
confidence: 93%
“…This result is not in agreement with some previous studies, which showed that the presence of TE in soil, among other environmental conditions, was susceptible to affecting EO composition and quality [ 22 , 24 ]. Notably, it was suggested that the stress induced by the presence of TE resulted in a modification of the secondary metabolism [ 24 , 49 , 50 , 51 ]. This could either lead to an inactivation of enzymes involved in the EO biosynthesis pathways, in the case of Mentha arvensis L., Mentha piperita L. and Vetiveria zizanioides Linn.…”
Section: Discussionmentioning
confidence: 99%
“…). Metal concentrations were defined as a function of toxicity levels, established by preliminary experiments and results reported in the literature for other species (ZHAO et al, 2010;VASSILEV et al, 2011;AMIRMORADI et al, 2012). Nutrient solutions were replaced once a week and the volume topped up daily.…”
Section: Growth Conditions and Treatmentsmentioning
confidence: 99%